IMPLEMENTASI UNDANG-UNDANG NOMOR 25 TAHUN 2009 TENTANG PELAYANAN PUBLIK DI KANTOR KECAMATAN BERGAS KABUPATEN SEMARANG PASCA PEMEKARAN - Fakih, Moh.; Tohari, Mohamad (Faculty of Social Science, Universitas Negeri Semarang, 2014)
For the agenda of generalization of local development and districtexpansion which is aimed to improvement of human resource creativity and levying of supporting facilities for requirement of public, the extension of Klepu district Semarang Regency is donewith Government Regulation of Republik Indonesia number 48 year of 1996 about forming of Pringapus district in Semarang Regency Central Java Province area. The purposes of this research are: to know and describe theimplementation process of Law Number 25 year of 2009, the factors or the resistances arising in implementation process of Law Number 25 year of 2009, and the efforts which are done by Head or officer of Bergas District Semarang Regency in maximizing the implementation process of Law Number 25 year of 2009.To reach the purposes, this research used qualitativedescriptive research method. That the public service in Bergas District office have been as according to Law number 25 year of 2009 and Government Regulation number 96 year of 2012. The factors or resistances for example policy of implementation regulation and technical regulation with tempo Â± 3 yearsperiod (in policy side).The limitation of good human resource as according to activity type of publicservice; supporting facilities, infrastructure and publication/socialization of implementation program of public service. The effort of District government officer with all the limitations is keep implementthe Law number 25 year of 2009 with result of assessment of service performance in same category between service implementer and receiver.Researchersuggests service standard and service communiquÃ© must be publicizedto public as service receiver, place the service implementer officer must have behavior and settlement of service counter space in level ofsub-district must be equalized and also coordination and communication need to be improved the implementation, so that public service can be enjoyed by service receiver.